PENDETEKSIAN DINI GEJALA COVID19 DENGAN METODE SKRINING KESEHATAN MENGGUNAKAN MEDIA WEBSITE - Novi Aryani Fitri (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
Background Health screening is the initial action taken by health workers for patients who come to the hospital or independently. This action will determine the next steps that can be seen in the screening assessment results, whether to be immediately referred to a special Covid-19 referral hospital, need to undergo initial tests, or can be examined in general according to complaints. Indonesia is the country with the most Covid19 cases in Southeast Asia. Where the high spread of the Covid19 virus is caused by the SARS-CoV-2 transmission process from patients that occurs through droplets that come out when coughing or sneezing. The purpose of this service is to detect early symptoms of Covid19 that are felt by the public based on current body temperature conditions, complaints that are felt, and travel history both out of town and abroad. The method used in this community service is to carry out health screening to detect early symptoms of Covid19. The media used is the website of the Pontianak Aisyiyah Polytechnic campus (Polita). The participants of the activity were all Pontianak people and its surroundings. This community service was carried out on March 21, 2020 to April 4, 2020. The results of the activity showed that the community was helped by the covid screening19. The public is also educated about the main symptoms of Covid19. Conclusion Health screening using the Polita website media is the right solution because it can be accessed publicly anywhere and anytime.